2021
DOI: 10.29219/fnr.v65.4527
|View full text |Cite
|
Sign up to set email alerts
|

Pentadecanoic acid promotes basal and insulin-stimulated glucose uptake in C2C12 myotubes

Abstract: Background: Saturated fatty acids (SFAs) generally have been thought to worsen insulin-resistance and increase the risk of developing type 2 diabetes mellitus (T2DM). Recently, accumulating evidence has revealed that SFAs are not a single homogeneous group, instead different SFAs are associated with T2DM in opposing directions. Pentadecanoic acid (C15:0, PA) is directly correlated with dairy products, and a negative association between circulating PA and metabolic disease risk was observed in epidemiological s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 21 publications
2
21
0
Order By: Relevance
“…72 Further, PA significantly stimulates basal glucose uptake and promotes insulin-induced glucose uptake in C2C12 myotubes. 73 In the current study, PA levels were reversed after 10-HDA administration. Thus, based on the above metabolomics results, we speculate that 10-HDA can regulate FAHFA (16:0/18:1) and PA metabolism to interfere with T2DM development.…”
Section: Discussionsupporting
confidence: 48%
“…72 Further, PA significantly stimulates basal glucose uptake and promotes insulin-induced glucose uptake in C2C12 myotubes. 73 In the current study, PA levels were reversed after 10-HDA administration. Thus, based on the above metabolomics results, we speculate that 10-HDA can regulate FAHFA (16:0/18:1) and PA metabolism to interfere with T2DM development.…”
Section: Discussionsupporting
confidence: 48%
“…Meta-analyses of cohort studies have previously reported an inverse relationship between biomarkers of dairy fat intake, particularly the C15:0 and C17:0, and the incident of T2D in humans (14,40). In vitro studies have also reported that C15:0 play a direct role in glucose metabolism via promoting GLUT4 translocation to plasma membrane in myotubes (41). C15:0 has also recently been proposed to be an essential fatty acid due to a number of established cardiometabolic benefits including attenuation of glucose concentrations in mice fed with high-fat diet (13).…”
Section: Dairy Fat and Its Impact On Glucose Metabolism And Insulin R...mentioning
confidence: 99%
“…According to Fu's procedure, 2-(N-[7-nitrobenz-2-oxa-1,3-diazol-4-yl] amino)-2-deoxyglucose (2-NBDG, Amgicam) was used to determine cellular glucose uptake. 29 C2C12 cells were differentiated in 96-well plates for 3 d and treated with different concentrations of HSYA for 24 h, or C2C12 cells were differentiated in 6-well plates for 3 d and transfected with siPPARδ as previously described, followed by treatment with 0.122 mg/mL of HSYA for 24 h. Then, the medium was replaced with serum-free DMEM containing 5 mM glucose. After 4 h incubation, the cells were incubated with the same medium containing 80 μM 2-NBDG with or without 100 nm insulin for 30 min at 37 °C.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%